(untitled) (Research, Society and Development, 2021)
Ocotea duckei Vattimo, popularly known as “louro-de-cheiro”, “louro-pimenta”, and “louro-canela” is a member of the Lauraceae family found in the Northeast region of Brazil. It is popularly used to treat neuralgia, dyspepsia, anorexia and pain. This current study aimed to promote the isolation and the identification / determination of new secondary metabolites of the species O. duckei Vattimo. In order to obtain the vegetable drug of O. duckei, its stem barks were harvested and submitted to a drying process followed by pulverization. The Crude Ethanolic Extract (BSE), obtained from the vegetable drug, was then subjected to an alkaloid extraction protocol in order to generate its Total Alkaloid Fraction (TAF). The isolation and identification of chemical compounds were carried out by chromatographic and spectroscopic methods respectively. The chemical investigation of O. duckei resulted in the isolation of three compounds: Ocoteaduccin A (OD-1, 0.020 g), Ocoteaduccin B (OD-2, 0.015 g), and N-methylcoclaurine (OD-3, 0.008 g). O. duckei proved to be a promising species, due to the variety of isolated chemical compounds. Further chemical, pharmacological and toxicological studies must be conducted in order to improve the phytochemical knowledge about this plant.